Single nucleotide polymorphism D1853N of the ATM gene may alter the risk for breast cancer - Schrauder, M.; Frank, S.; Strissel, Pamela; Lux, Michael P.; Bani, Mayada; Rauh, C.; Sieber, Cornel; Heusinger, K.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strick, Reiner; Beckmann, Matthias; et al. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose Various ATM (ataxia telangiectasia-mutated) mutations and polymorphisms have been reported to be associated with an increased breast cancer risk. Recent studies have produced contradictory results regarding the association between ATM genetic variants and breast cancer risk.Materials and methods The common ATM polymorphism 5557G > A (p.D1853N) (rs1801516), previously suggested to be associated with bilateral breast cancer, was analyzed using real-time PCR in 514 unselected patients with breast cancer and 511 age-matched healthy control individuals. DNA was obtained from peripheral blood draw.Results The ATM genotype was weakly associated with the risk for breast cancer (P = 0.04 for the overall test). The odds ratio for women with a heterozygous genotype was 0.70 (95% CI, 0.52-0.94) and for the homozygous variant 0.63 (95% CI, 0.27-1.49). Disease-free survival and overall survival showed no significant association with specific genotypes.Conclusions The results of this study might suggest a minor association between polymorphism 5557G > A and a reduced risk of breast cancer.
Keywords: TM gene variants; polymorphism; breast cancer; DNA damage; epidemiology; association